2015
DOI: 10.1021/acs.jafc.5b01530
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Herbicidal Activity of Triketone–Quinoline Hybrids as Novel 4-Hydroxyphenylpyruvate Dioxygenase Inhibitors

Abstract: 4-Hydroxyphenylpyruvate dioxygenase (EC 1.13.11.27, HPPD) is one of the most important targets for herbicide discovery. In the search for new HPPD inhibitors with novel scaffolds, triketone-quinoline hybrids were designed and subsequently optimized on the basis of the structure-activity relationship (SAR) studies. Most of the synthesized compounds displayed potent inhibition of Arabidopsis thaliana HPPD (AtHPPD), and some of them exhibited broad-spectrum and promising herbicidal activity at the rate of 150 g a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 32 publications
3
96
0
Order By: Relevance
“…The molecules were constructed by the default settings of SYBYL 6.91 software (Tripos Inc.) and optimized with the steepest‐descent algorithm to a convergence criterion of 0.005 kcal mol −1 . The CoMFA steric and electrostatic field energies were calculated by the SYBYL default parameters; an sp 3 carbon probe atom with a charge of +1, 2.0 Å rid points spacing, an energy cutoff of 30.0 kcal mol −1 and a minimum σ (column filtering) of 2.0 kcal/mol …”
Section: Methodsmentioning
confidence: 99%
“…The molecules were constructed by the default settings of SYBYL 6.91 software (Tripos Inc.) and optimized with the steepest‐descent algorithm to a convergence criterion of 0.005 kcal mol −1 . The CoMFA steric and electrostatic field energies were calculated by the SYBYL default parameters; an sp 3 carbon probe atom with a charge of +1, 2.0 Å rid points spacing, an energy cutoff of 30.0 kcal mol −1 and a minimum σ (column filtering) of 2.0 kcal/mol …”
Section: Methodsmentioning
confidence: 99%
“…Among them, triketone HPPD herbicides with triketone and aromatic moieties are the most widely studied . For example, many studies have reported that the modification of the aromatic part of triketone derivatives is an effective way to obtain new inhibitors with improved potency. All the modified triketone derivatives mainly focused on aromatic component, which is replaced by heterocycles, aliphatic side chains, fused heterocycles and fused aromatics …”
Section: Introductionmentioning
confidence: 99%
“…) . Among them, mesotrione (Scheme ) is a highly successful representative triketone HPPD herbicide . Established structure–activity relationships indicate that the 2‐benzoylethen‐1‐ol substructure is required for potent HPPD inhibition (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the benzene ring of existing triketone HPPD herbicides has been an effective method of obtaining new HPPD inhibitors. Modified benzene rings of these novel HPPD herbicides include: benzo[ d ]oxazol‐2(3 H )‐one, 2,3‐dihydrobenzo[ b ]thiophene‐1,1‐dioxide, 4 H ‐thiochromene, quinoline, aryloxymethylene and quinazoline‐2,4(1 H ,3 H )‐dione …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation